2012
DOI: 10.1002/hep.25614
|View full text |Cite
|
Sign up to set email alerts
|

Liver progenitor cell markers correlate with liver damage and predict short-term mortality in patients with alcoholic hepatitis

Abstract: Alcoholic hepatitis (AH) is a severe condition developed in patients with underlying alcoholic liver disease. Ductular reaction has been associated with chronic alcohol consumption but there is no information regarding the extent of liver progenitor cell (LPC) proliferation in AH. The aim of this study was to investigate LPC markers in AH and its correlation with disease severity. Fifty-nine patients with clinical and histological diagnosis of AH were included in the study. LPC markers were assessed by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
175
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(190 citation statements)
references
References 32 publications
8
175
0
2
Order By: Relevance
“…Our histological results are in line with previous data in alcoholic [18,35,36], metabolic [36][37][38] or viral [34] liver disease, which demonstrated that high liver total K7 expression parallel disease severity as assessed by the MELD score. Indeed, LPC are known to expand from the ductular reaction, the intrahepatic stem cell compartment, into the liver lobule when mature hepatocytes are not able to bring full regeneration following severe injury [52], particularly in the setting of ACLF [12].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our histological results are in line with previous data in alcoholic [18,35,36], metabolic [36][37][38] or viral [34] liver disease, which demonstrated that high liver total K7 expression parallel disease severity as assessed by the MELD score. Indeed, LPC are known to expand from the ductular reaction, the intrahepatic stem cell compartment, into the liver lobule when mature hepatocytes are not able to bring full regeneration following severe injury [52], particularly in the setting of ACLF [12].…”
Section: Discussionsupporting
confidence: 92%
“…Other baseline and dynamic models are currently under investigation [46]. When applying another more restrictive criterion (90-day mortality) as evaluated in another study [18], we also found a significant increase in proliferative LPC and hepatocyte number in patients alive compared to patients who died during this 3-month follow-up (Supplementary table 5). Hepatic gene expression profile also differentiates improvers from non-improvers.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Given that AH is associated with marked dysregulation of progenitor cells and impaired liver regeneration [18, 19], this provides a biologically plausible hypothesis where alcohol cessation may conceivably cause short-term deterioration in liver function. This is consistent with our data that confirm that a proportion of patients have cut down or stopped drinking before coming unwell.…”
Section: Discussionmentioning
confidence: 99%